Pengaruh Promosi dan Harga Terhadap Minat Pembelian Tiket Pesawat Pada Maskapai Lion Air di Bandar Udara Soekarno-Hatta - Raynaldy Gilbert Perdana (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the era of globalization, technology is developing very rapidly in line with the needs of today's society. The rapid development of technology today is very helpful for people's activities in terms of knowing information from various worlds, news and data transmission. This research focuses on the promotions provided and the prices offered by Lion Air. This study aims to determine how positive the impact of promotions and prices offered so that many are interested in buying tickets on Lion Air Airlines. The method used is a statistical method with a quantitative research design. The data collection technique is by distributing questionnaires. The data collection instrument used a Likert scale. Researchers used data analysis techniques with 2 tests, namely: instrument testing and hypothesis testing. In the instrument test there is an i test of validity and reliability, and in the hypothesis test there is an t test, an f test, a test of the coefficient of determination (R2), and multiple linear regression tests. The results of this study state that promotions and prices have a positive influence in increasing ticket buying interest on Lion Air Airlines